Obstetrics and gynecology at a glance - Norwitz, Errol R.; Schorge, John O. (At a glance series, 2010)
"The at a Glance series is popular among medical students and junior doctors for its concise and simple approach and excellent illustrations, Each bite-sized chapter is covered in a double-page spread with colour summary diagrams on the left page and explanatory text on the right. Covering a wide range of topics, books in the at a Glance series are ideal as introductory subject texts or for revision purposes, and are useful throughout medical school and beyond. Everything you need to know about Obstetrics and Gynecology... at a Glance!" "Following the familiar, easy-to-use at a Glance format, and now in full-colour, Obstetrics and Gynecology at a Glance is an accessible introduction and revision text for medical students. Fully revised and updated to reflect changes to the content and assessment methods used by medical schools, this at a Glance provides a user-friendly overview of obstetrics and gynecology to encapsulate all that the student needs to know. It is an invaluable resource for all medical students, junior doctors, nurses and midwives who need an introduction to obstetrics and gynecology."